Pendampingan Pertukaran Mahasiswa Merdeka: Shankara Polines - Yusuf Hendrawanto; Bagas Putra Pradana; Aditya Rizqi Senoaji; Rangga Permana; Moh. Muslikh; Eri Prihatmini (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The Pertukaran Mahasiswa Merdeka (PMM) program is a flagship scheme of the Merdeka Belajar–Kampus Merdeka (MBKM) initiative designed to strengthen students' national insight, tolerance, and socio-cultural adaptation. This community service project aims to describe the process and outcomes of PMM mentoring through the Shankara group at Politeknik Negeri Semarang (Polines) in 2024. The implementation method adopted a participatory approach comprising three main stages: planning and local potential mapping, execution of 16 Modul Nusantara activities, and monitoring and evaluation based on the Kirkpatrick model. The mentoring results indicate that the Shankara group successfully integrated the full series of activities, which consisted of: 8 diversity activities, 5 reflection activities, 2 inspiration activities, and 1 social contribution activity across the Central Java and DIY regions. The diversity and inspiration activities proved effective in broadening cross-cultural perspectives and motivating participants' entrepreneurial spirit. Reflection sessions deepened the meaning derived from these experiences, while the social contribution action at Kalitalang Ecotourism in Klaten delivered a practical impact for the local community. Overall, this structured mentoring effectively facilitated the transformation of students' attitudes from an ethnocentric to an ethnorelative stage while strengthening a shared national identity.